2024
DOI: 10.2174/1574886318666230331112800
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape on Development of Phenylalanine and Toxicity of its Metabolites - A Review

Abstract: Phenylalanine, an essential amino acid, is the "building block" of protein. It has a tremendous role in different aspects of metabolic events. The tyrosine pathway is the prime one and is typically used to degrade dietary phenylalanine. Phenylalanine exceeds its limit in bodily fluids and the brain when the enzyme, phenylalanine decarboxylase, phenylalanine transaminase, phenylalanine hydroxylase (PAH) or its cofactor tetrahydrobiopterin (BH4) is deficient causes phenylketonuria, schizophrenia, attention-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…23 27 28 Experimental studies have shown that hyperphenylalaninaemia can induce oxidative stress, inflammation, mitochondrial dysfunction and neuronal apoptosis. [29][30][31][32][33] Hence, it is important to weigh the risks and benefits of commencing PN very early in the neonatal period.…”
Section: What This Study Addsmentioning
confidence: 99%
“…23 27 28 Experimental studies have shown that hyperphenylalaninaemia can induce oxidative stress, inflammation, mitochondrial dysfunction and neuronal apoptosis. [29][30][31][32][33] Hence, it is important to weigh the risks and benefits of commencing PN very early in the neonatal period.…”
Section: What This Study Addsmentioning
confidence: 99%